Style Matters: Manuscript requirements: the advance from Vancouver - Huth, Edward (1981)
The agreement on uniform requirements for manuscripts developed in January 1978 in Vancouver, British Columbia, by a small group of clinical editors is now adhered to by more than 130 journals. This development was reported at a meeting of the International Committee of Medical Journal Editors held at Leeds Castle, Kent, England, in October 1980. Suggestions for revision of the requirements document were reviewed, and closer consideration of possible changes was scheduled for October 1981.